Korruption im internationalen Sport: ökonomische Analyse und Lösungsansätze - Wolfgang Maennig (Vierteljahrshefte zur Wirtschaftsforschung, 2004)
Korruption im (internationalen) Sport ist nichts Neues. Olympische Fälle sind seit 388 v. Chr. dokumentiert. In der jüngeren Vergangenheit ragen der Korruptionsskandalim College-Basketball in den USA von 1951, der Fußball-Bundesliga-Bestechungsskandal von 1971 und der Skandal um die Vergabe der Olympischen Winterspiele 2002 an Salt Lake City heraus. Der vorliegende Beitrag zeigt, dass Korruption im Sport - wie in anderen Bereichen menschlicher Aktivitäten - einer ökonomischen Analyse zugänglich ist. Aus dieser ökonomischen Analyse heraus lassen sich Erkenntnisse ableiten, die die bisher ergriffenen, meist von Expertenaus den Gebieten der Jurisprudenz, der Politikwissenschaft und der Pädagogik erarbeiteten Maßnahmen sinnvoll ergänzen können. Maßnahmen zur Verringerung der Renten im Sport, zur Vergrößerung der Transparenz bei Vergabeentscheidungen sowie monetäre Disincentives gegen korruptives Verhalten erweisen sich als besonders sinnvoll. – – Corruption is no new phenomenon in international sports. In the first documented case, the athlete Eupolos from Thessalia bribed three of his competitors in fist fightingat the Olympic games of 388 B.C. In modern sports, well documented cases of corruption are e.g the college basketball scandal in the USA in 1951, and the scandal in German soccer Bundesliga in 1971, and the case of the IOC in 1998/1999, concentrated around the bidding process for the Olympic Winter Games of 2002 inSalt Lake City, USA. This article shows that corruption in sports is - as in other areas of human activities - accessible for an economic analysis. From such an analysis informations can be deduced which may enhance the anticorruption measures which - up to now - have been worked out and implemented mainly by experts from law, policy and pedagogy. Measures which reduce the rents in sports, which enhance transparency and monetary disincentives against corruptive behaviour are especially efficient. It is noticeable that - in spite of the obviously high degree of economic determination of the problems - in all cases relatively little use has so far been made of economic instruments during the elaboration of counter-measures. The usual, most prominent reactions were bans for officials and/or athletes, for a limited time or for lifetime. These bans were accommodated by other measures of order policy. For example, in the case of the IOC scandal, membership in the IOC was limited to eight years (with the possibility of reelection), the age limit was lowered to 70, the host city election procedure was overhauled to ensure that only cities adequately prepared will be authorized to go forward into the full bid process, and there is now a ban on members travelling to the applicant cities. Furthermore, since 2003, the IOC ethic code now also applies to bidding cities. The case of the IOC is a good one to show that - althoughthe sports federations in general underwent transformations in a shorttime which would almost seem impossible for any other comparable national or international organisation the measures might becriticised and enhanced from an economic point of view.
Keywords: 330; Sport; International; Korruption; Sportökonomik